2011
DOI: 10.1177/147323001103900552
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation-Induced Seizure of a Patient with Adolescent-Onset Depression: A Case Report and Literature Review

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has been used as an investigative and therapeutic tool in neuropsychiatry and is advocated as a therapy for the treatment of psychiatric disorders, particularly adult depression. The therapeutic efficacy of current antidepressants applied to children or adolescents is unsatisfactory; thus innovative treatments such as rTMS are in demand. Large-scale clinical studies are required to determine the safety of rTMS for this age group. The present case report descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 26 publications
1
30
1
1
Order By: Relevance
“…She did not have further seizures. Authors noted that the concurrent use of sertraline may have reduced the seizure threshold in this patient (Hu et al 2011). Chiamberro et al (2013) reported on a 16-year-old girl with depression (concurrently treated with sertraline, olanzapine, and hydroxyzine, also with limited benefit) who was initiated in a repetitive TMS treatment protocol using the figure-8 coil over the dorsolateral prefrontal cortex, at 10 Hz, with 60 trains of 5-second duration, 25-second intertrain interval, and 3000 stimuli per day, 5 days a week.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…She did not have further seizures. Authors noted that the concurrent use of sertraline may have reduced the seizure threshold in this patient (Hu et al 2011). Chiamberro et al (2013) reported on a 16-year-old girl with depression (concurrently treated with sertraline, olanzapine, and hydroxyzine, also with limited benefit) who was initiated in a repetitive TMS treatment protocol using the figure-8 coil over the dorsolateral prefrontal cortex, at 10 Hz, with 60 trains of 5-second duration, 25-second intertrain interval, and 3000 stimuli per day, 5 days a week.…”
Section: Discussionmentioning
confidence: 79%
“…Hu et al (2011) reported on a 15-year-old female with depression (concurrently taking sertraline with limited benefit) who was initiated on a repetitive TMS protocol with the figure-8 coil over the left dorsolateral prefrontal cortex at 100% of resting MT, 10 Hz, 60 trains of 5-second duration, 25-second intertrain interval, and 3000 total pulses. During the first treatment, she had a generalized, tonic-clonic seizure.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, eight published manuscripts were case reports [44, 6470]. Three publications, one on tDCS [23] and two on TMS [66, 71], did not report the adverse effects of NIBS modalities, nor was the information available from the corresponding authors or ClinicalTrials.gov.…”
Section: Resultsmentioning
confidence: 99%
“…rTMS was the most frequently examined NIBS modality, with 35 publications addressing the application of TMS on children and adolescents (3.0 to 17.8 years old) [3840, 4446, 52, 5557, 6467, 70, 71, 73, 7581, 83, 8594]. The duration of the interventions ranged from one day to 18 weeks, and the stimulation provided was administered in frequencies ranging from 0.3Hz to 10Hz; two studies reported priming the subject with a frequency of 6Hz before the procedure [46, 52].…”
Section: Resultsmentioning
confidence: 99%
“…49 Transcranial magnetic stimulation is another potential treatment for resistant depression but there have been a few case reports of seizures. 30,50 More studies are required to assess the effectiveness and safety of these techniques for treating depression in individuals with epilepsy.…”
Section: Management Of Depression In Epilepsymentioning
confidence: 99%